Social Desirability Bias Impacts Self‐Reported Alcohol Use Among Persons With HIV in Uganda. (11th November 2019) - Adong, Julian; Fatch, Robin; Emenyonu, Nneka I.; Cheng, Debbie M.; Muyindike, Winnie R.; Ngabirano, Christine; Kekibiina, Allen; Woolf‐King, Sarah E.; Samet, Jeffrey H.; Hahn, Judith A.
Abstract : Background: Self‐report is widely used to assess alcohol use in research and clinical practice, but may be subject to social desirability bias. We aimed to determine if social desirability impacts self‐reported alcohol use. Methods: Among 751 human immunodeficiency virus (HIV)‐infected patients from a clinic in southwestern Uganda, we measured social desirability using the Marlowe–Crowne Social Desirability Scale (SDS) Short Form C, self‐reported alcohol use (prior 3 months) Alcohol Use Disorders Identification Test—Consumption (AUDIT‐C), and phosphatidylethanol (PEth), a biomarker of prior 3 weeks' drinking. We conducted multiple regression analyses to assess the relationship between SDS score (low, medium, and high levels) and (i) any self‐reported recent alcohol use, among those who were PEth‐positive (≥8 ng/ml), and (ii) continuous AUDIT‐C score, among those reporting any recent alcohol use. We controlled for PEth level, age, gender, education, economic assets, marital status, religion, spirituality/religiosity, social support, and study cohort. Results: Of 751 participants, 59% were women; the median age was 31 years (interquartile range [IQR]: 26 to 39). Median SDS score was 9 (IQR: 4 to 10). Two‐thirds (62%) self‐reported any recent alcohol use; median AUDIT‐C was 1 (IQR: 0 to 4). Among those who were PEth‐positive (57%), 13% reported no recent alcohol use. Those with the highest SDS tertile had decreased odds of reporting any recent alcohol use compared to the lowest tertile, but the association did not reach statistical significance in multivariable analyses (adjusted odds ratio 0.55 [95% confidence interval (CI): 0.25, 1.23]). Among participants self‐reporting recent alcohol use, SDS level was negatively associated with AUDIT‐C scores (adjusted β : −0.70 [95% CI: −1.19, −0.21] for medium vs. low SDS and −1.42 [95% CI: −2.05, −0.78] for high vs. low SDS). Conclusions: While use of objective measures (e.g., alcohol biomarkers) is desirable for measuring alcohol use, SDS scores may be used to adjust self‐reported drinking levels by participants' level of social desirability in HIV research studies. Abstract : We evaluated associations of social desirability (SDS) with self‐reported alcohol use among HIV‐positive participants in Uganda while controlling for phosphatidylethanol (PEth). Biomarker‐confirmed drinkers with high SDS scores had lower odds of reporting alcohol use compared to those with low SDS scores (Figure 1). Among participants reporting recent alcohol use, higher SDS scores were associated with lower AUDIT‐C scores (Figure 2). Social desirability is an important component of alcohol use reporting; adjusting for SDS analytically in research studies may be needed.